Evaluasi Kebijakan Percepatan Penurunan Stunting Di Kecamatan Candi Kabupaten Sidoarjo - Daniela Elisandra; Anggraeny Puspaningtyas; M Kendry Widiyanto (Journal of Research and Development on Public Policy, 2024)
The number of stunting cases in Candi District has increased from 270 cases in 2022 to 485 cases in 2023 as of September. The aim of this research is to analyze policy evaluation using evaluation indicators according to William N Dunn (2003;610), namely; Effectiveness, Efficiency, Adequacy, Evenness, Responsiveness and Accuracy, as well as supporting and inhibiting factors for implementing policies to accelerate stunting reduction in Candi District, Sidoarjo Regency. This research uses qualitative research methods with a descriptive approach. Based on the research results, the implementation is still not going well and is less than optimal. This is because there are still complaints about infrastructure or facilities, lack of coordination and commitment between Regional Apparatus Organizations, limited budget funds, lack of community participation and inaccuracies in the delivery of socialization materials. Supporting factors for the Accelerated Stunting Reduction Policy in Candi District include; coordination and commitment of policy implementers, competent communication and human resources, active community participation, access to clean water, mindset and parenting patterns of parents, economic factors, monitoring and evaluation systems, adequate budget funds and good and appropriate communication of policy implementers. Meanwhile, inhibiting factors in implementing this policy include; there is inappropriate provision and misuse of aid, data validation errors, lack of coordination and commitment between Regional Apparatus Organizations.